TREND ASSESSING USING MANN-KENDALL’S TEST FOR PRIŠTINA METEOROLOGICAL STATION TEMPERATURE AND PRECIPITATION DATA, KOSOVO AND METOHIJA, SERBIA - Bačević, Nikola R; Pavlović, Milica; Rasljanin, Ilhana (Bulletin of Natural Sciences Research, 2018)
The study includes statistical analysis of Priština meteorological station data on temperature and precipitation trends. The data are organized into four time series: average annual air temperatures (Ta), average maximal annual air temperatures (Tamax), average minimal annual air temperatures (Таmin), as well as annual precipitation sums (RRsum), all in the period 1949 – 1999. The Mann-Kendallʹs (MK) trend test analysis of the corresponding hypotheses discloses that the H0 hypothesis should be accepted.  The general conclusion is that there is no trend neither in maximal, minimal, average temperatures, nor in average annual precipitation for the 1949 – 1999 period for the central Kosovo and Metohija (K&M).
Keywords: Air temperature trend; Mann-Kendall; Precipitation trend; Priština; Kosovo and Metohija; Serbia